2001
DOI: 10.1034/j.1399-0004.2001.590610.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin‐1 (FBN1) gene frameshift mutations in Marfan patients: genotype–phenotype correlation

Abstract: Marfan syndrome (MFS) is a multisystemic disease associated with mutations in the fibrillin-1 gene. Most of the reported mutations are missense substitutions mainly affecting the epidermal growth factor (EGF)-like protein domain structure and the calcium-binding (cb) site. The aim of our study was to investigate the correlation between fibrillin-1 frameshift mutations and the clinical phenotype in patients affected by MFS. In 48 out of 66 Marfan patients a pathogenetic mutation was found. We detected novel mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
4
19
1
Order By: Relevance
“…Certain mutations within exons 1-10 have been associated with significant cardiovascular pathology [Attanasio et al, 2008]. Neonatal Marfan syndrome and severe Marfan syndrome are associated with missense mutations in exons 24-40 [Pepe et al, 2001;Turner et al, 2009], which affect the 8-Cys motif and cbEGF domains 11-18 [Hirani et al, 2008]. Neonatal Marfan syndrome is most strongly associated with missense mutation in exons 24-27 and 31-32 [Palz et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain mutations within exons 1-10 have been associated with significant cardiovascular pathology [Attanasio et al, 2008]. Neonatal Marfan syndrome and severe Marfan syndrome are associated with missense mutations in exons 24-40 [Pepe et al, 2001;Turner et al, 2009], which affect the 8-Cys motif and cbEGF domains 11-18 [Hirani et al, 2008]. Neonatal Marfan syndrome is most strongly associated with missense mutation in exons 24-27 and 31-32 [Palz et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Rare DNA variants that alter single amino acid residues within the coding sequence of the protein (missense mutations) are the cause of 50-66% of cases of Marfan syndrome [Attanasio et al, 2008;Turner et al, 2009]. Though fewer than 15% of documented cases are the result of deletion/insertion mutations [Pepe et al, 2001;Turner et al, 2009], this proportion is expected to increase as high-throughput methodologies that detect these variants become more widespread.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the quantitative mRNA expression of the mutant allele [17], it is difficult to know the effect of novel mutation and what will be the phenotype. There have been many attempts to clarify the relationship between the genotype and phenotype in Korean patients with MFS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that mutations in FBN1 frequently occur in exons 2, 15, 22, 27, 46, 55, and 62 (Faivre et al, 2008) rather than exon 19 (Micheal et al, 2012). To date, only 5 mutations have been identified in exon 19, including a frameshift mutation (2412delAT) observed in one Italian patient with clinical symptoms mainly involving the skeletal and cardiovascular systems (Pepe et al, 2001), 3 missense mutations in 3 sporadic patients (p.C781R, p.C781R, p.C776Y) in patients from Belgium with classical MFS and involvement of the cardiovascular system (Loeys et al, 2001), and a heterozygous missense mutation (c.2368T>A p.C790S) in all affected members presenting ectopia lentis, myopia, and glaucoma, but lacking the cardinal cardiovascular features of MFS in a large Pakistani family (Micheal et al, 2012). In our study, the novel heterozygous missense mutation c.2243 T>G (p.C781W) in exon 19 of FBN1 was identified in all patients in the pedigree.…”
Section: Discussionmentioning
confidence: 99%